Fenomena Campur Kode Dan Alih Kode Dalam Praktik Komunikasi Multibahasa Masyarakat Perkotaan - Alifia Sastia Febriana Resky (CV. SINAR HOWUHOWU, 2026)
Urban communities constitute social spaces characterized by diverse cultural and linguistic backgrounds, which encourage the emergence of multilingual communication practices in everyday life. This condition gives rise to the phenomena of code-mixing and code-switching as commonly used communication strategies among speakers. This study aims to examine the forms, functions, and factors influencing the occurrence of code-mixing and code-switching in the communication practices of urban communities. The research employs a qualitative approach with a descriptive design. Data were collected through participant observation, semi-structured interviews, and recording techniques involving urban community members who use more than one language in their interactions. Data analysis was conducted by classifying forms of code-mixing and code-switching and examining their social functions and contextual usage based on sociolinguistic theories. The results indicate that code-mixing is more dominant than code-switching, with word and phrase insertions being the most frequently observed patterns. Indonesian functions as the primary language, combined with regional languages and foreign languages, particularly English. Code-switching occurs in response to changes in participants, situations, and communication purposes. This study concludes that code-mixing and code-switching reflect speakers’ linguistic flexibility and social competence in navigating the dynamics of multilingual communication in urban societies.